Rancang Sistem Lampu Pintar Otomatis Menggunakan IoT - S Nurmuslimah; Wahyu Widodo; Zulvia Eksanti (Institut Teknologi Adhi Tama Surabaya, 2023)
This study described a light control system prototype using a Nodemcu microcontroller and based on mobile Android. Home lights are one of the biggest contributors to electricity consumption. Less efficient lamps cause electricity waste, which can eventually increase electricity bills. Most home lighting control systems still use manual switches that are permanently attached to each switch panel. Waste of electricity is often caused by forgetting to turn off the lamps. Therefore, this study developed a prototype lamp control system to save electricity and make it easier for room occupants to use lights. This controller can control a lamp remotely using only a smartphone. The lamp controller has features such as brightness control, human presence detection, turning on or off, and monitoring. This research employed the MCU node, or microcontroller, as the brain of the prototype, or the tool that would be used. The ESP8266 served to send sensor data to the server; the PIR sensor functioned as a human detection sensor; the relay acted as a component on or off control. After designing and testing this system using the Quality of Service (QOS) through the Wireshark application, the results obtained an average throughput of 43.95 Kbit/s, a delay of 100.09 m/s, jitter of 100.82 m/s, and 0% packet loss. In terms of the accuracy test of the sensor in reading the data, the average value was very good at 100%. This value was derived from five PIR sensor tests at different distances.